Neurocognitive Profiling of Adult Treatment Seekers Enrolled in a Clinical Trial of a Web-delivered Intervention for Substance Use Disorders. Issue 2 (March 2018) - Aharonovich, Efrat; Campbell, Aimee N.C.; Shulman, Matisyahu; Hu, Mei-Chen; Kyle, Tiffany; Winhusen, Theresa; Nunes, Edward V.
Abstract : Objective: This study is a secondary descriptive analysis that explores and compares the cognitive profiles of adults entering treatment at geographically diverse community-based substance use disorder treatment facilities. Methods: Performance on cognitive measures at baseline was compared across 5 primary substance subgroups of individuals (alcohol = 104; cocaine = 102; stimulants = 69; opioids = 108; marijuana = 114) enrolled in a web-based psychosocial treatment study conducted within the National Drug Abuse Treatment Clinical Trials Network. MicroCog subtests were used to assess cognitive domains of attention and mental control, reasoning and cognitive flexibility, and spatial processing. Results: The average age of onset for a substance use disorder was early to mid-20s, with marijuana users reporting the earliest age of onset (mean 19.9, SD 7.5) and stimulant users reporting the latest (mean 25.2, SD 9.9). Among the total sample, half (49.7%) demonstrated impairment in cognitive flexibility and reasoning, and over one-third (37.3%) had impairment in verbal learning and memory. Stimulant (37.68%) and cocaine (34.31%) users showed significantly greater clinical impairment in attention and mental control compared with alcohol users (17.31%) and opioid (21.30%) users (stimulant subgroup only) (χ 2 [4] = 10.97, P  = 0.027). Cocaine users showed the greatest overall impairment across total and proficiency subtest scores, although these were not statistically different from other subgroups. Conclusions: These findings confirmed previous studies, indicating a high prevalence of significant cognitive dysfunction across all substance use categories among treatment-seeking adults, and found that cocaine use appears to be associated with the most impairment. Increasing knowledge of similarities and differences between primary substance subgroups can help guide substance use disorder treatment planning.